What is the Role of Cangrelor in Patients Undergoing PCI? - Droppa, Michal; Geisler, Tobias (Current Vascular Pharmacology, 2018)
Dual antiplatelet therapy with aspirin and oral P2Y12-receptor inhibitors prevents ischemic events in patients undergoing Percutaneous Coronary Intervention (PCI). However, oral administration of antiplatelet drugs cause delay of onset of platelet inhibition in P2Y12-inhibitor naïve patients. Cangrelor is a novel P2Y12-receptor inhibitor which is administrated intravenously and thus allows immediate antiplatelet inhibition during PCI. Due to its unique pharmacokinetics with fast onset of platelet inhibition and very short plasma half-life it allows effective and controllable periprocedural platelet inhibition. It could reduce short-term ischemic events in large randomized clinical trials. The present article reviews the available evidence and application on cangrelor use in clinical practice.
Keywords: platelet inhibition